PENDAMPINGAN TUKANG RELIEF BANGUNAN DI DESA UTEUNKOT KOTA LHOKSEUMAWE - Teuku Mudi Hafli; F Fasdarsyah; David Sarana (Yayasan Hurriah, Banda Aceh, 2022)
Uteunkot is one of the villages in Lhokseumawe City which is one of the fostered villages of Malikussaleh University. As time went on, the increase in population had an effect on changes in land use in Uteukot Village, at first a lot of land was dormant and not used, but with the increasing number of requests for residential houses and boarding houses, there were an increasing number of residential buildings in Uteunkot Village. With the addition of boarding houses or dwellings in the village of Uteunkot, the builders, especially relief workers, were not matched to beautify the appearance of the dwellings or boarding houses in the village. Relief is a sculptural art that is usually done on wood or stone media. Relieving is a job in the construction field that is the most difficult, because it requires perseverance, patience, accuracy and skill. Therefore, a training in the process of making reliefs is needed for builders in the village of Uteunkot. The method used in this activity is to conduct counseling in the form of providing theoretical views regarding positive impacts in the field of relief and relief structures of buildings. After conducting counseling, the training will be continued by installing good and correct reliefs.